2018
DOI: 10.17843/rpmesp.2018.352.3140
|View full text |Cite
|
Sign up to set email alerts
|

Identificación y determinación estructural de un sesquiterpeno de las hojas de Tessaria integrifolia Ruiz & Pav. y evaluación de su actividad Leishmanicida

Abstract: Fluid extract of leaves of Tessaria integrifolia Ruiz & Pav. presents leishmanicidal activity on Mesocricetus auratus with experimental leishmaniasis. Fraction F8 presents leishmanicidal activity on infected macrophages at a dose of 14 μg/mL. An eudesman type sesquiterpene was identified, according to 1 H, 13C, and LC / MS NMR analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
2
Order By: Relevance
“…The cytotoxicity of this saponin was not reported (Khanna et al, 2009). Similarly, Silva-Correa et al (2018) identified an eudesman type sesquiterpen [(4αS, 5R,6R,8αR)-6-hidroxi-5,8α-dimetil-3-(1-metiletiliden) octahidronaftalen-2(1H)-ona)] as the active compound related to the leishmanicidal activity of Tessaria integrifolia Ruiz & Pav in Mesocricetus auratus infected with Leishmania sp. (Silva-Correa et al, 2018).…”
Section: Other Compounds From Asteraceae Plants With Activity Againstmentioning
confidence: 97%
“…The cytotoxicity of this saponin was not reported (Khanna et al, 2009). Similarly, Silva-Correa et al (2018) identified an eudesman type sesquiterpen [(4αS, 5R,6R,8αR)-6-hidroxi-5,8α-dimetil-3-(1-metiletiliden) octahidronaftalen-2(1H)-ona)] as the active compound related to the leishmanicidal activity of Tessaria integrifolia Ruiz & Pav in Mesocricetus auratus infected with Leishmania sp. (Silva-Correa et al, 2018).…”
Section: Other Compounds From Asteraceae Plants With Activity Againstmentioning
confidence: 97%
“…Similarmente la actividad leishmanicida fue evaluada contra promastigotos de Leishmania amazonensis con pobre citotoxicidad, evaluados en macrófagos (19). El extracto fluido de hojas de Tessaria integrifolia presenta actividad leishmanicida sobre Mesocricetus auratus (20). Bajo estas condiciones experimentales, se concluye que los extractos metanólicos de Piper aduncum (matico), Eucalyptus globulus (eucalipto) y Púnica granatum (granado) mostraron moderado efecto antileishmaniásico in vitro, y que la producción de óxido nítrico es uno de los probables mecanismos de acción para Púnica granatum (21) No hubo evidencia de toxicidad aguda causada por ninguno de los 2 extractos, en la dosis máxima administrada por vía oral y equivalente a 10 y 15,67 g de material vegetal/kg (20).…”
Section: Especiesunclassified
“…El extracto fluido de hojas de Tessaria integrifolia presenta actividad leishmanicida sobre Mesocricetus auratus (20). Bajo estas condiciones experimentales, se concluye que los extractos metanólicos de Piper aduncum (matico), Eucalyptus globulus (eucalipto) y Púnica granatum (granado) mostraron moderado efecto antileishmaniásico in vitro, y que la producción de óxido nítrico es uno de los probables mecanismos de acción para Púnica granatum (21) No hubo evidencia de toxicidad aguda causada por ninguno de los 2 extractos, en la dosis máxima administrada por vía oral y equivalente a 10 y 15,67 g de material vegetal/kg (20). Además de los componentes farmacológicamente activos, determinantes de la acción que producirán, contienen otros compuestos químicos que pueden influir en su actividad (coadyuvantes), por ejemplo, modulando su biodisponibilidad o la estabilidad, así como materiales inactivos o inertes y, a veces, constituyentes potencialmente alergénicos o tóxicos (22).…”
Section: Especiesunclassified
“…Notably, the methanolic extract of T. integrifolia leaves contains phenolic compounds, eudesmanes, caffeolic acid, lignans, sesquiterpenes, and flavonoids [ 16 ]. Furthermore, a eudesmane-type compound with leishmanicidal activity has been reported in the fluid extract of its leaves [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly found in vegetation along rivers in Peru's coastal and jungle regions [12]. Known for its medicinal properties, including antiulcer, antiasthmatic, leishmanicidal, antipyretic, antispasmodic, diuretic, and anti-inflammatory effects, this plant species has Available at www.veterinaryworld.org/Vol.16/September-2023/20.pdf been used to induce analgesia when treating liver and kidney stones [13]. Chemical compounds, such as caffeoylquinic acid, eudesmane derivatives, flavones, sesquiterpenes, lignans, α-terthienyl, bisthenyl derivatives, β-amyrin acetate, and squalene, have been found in the roots, stems, leaves, and flowers of T. integrifolia [14,15].…”
Section: Introductionmentioning
confidence: 99%